Conceptualizing music: Cognitive structure, theory, and analysis - Zbikowski, Lawrence (Oxford Oxford university press, 2005)
This book shows how recent work in cognitive science, especially that developed by cognitive linguists and cognitive psychologists, can be used to explain how we understand music. The book focuses on three cognitive processes--categorization, cross-domain mapping, and the use of conceptual models--and explores the part these play in theories of musical organization.